Thermal Pre-treatments of Woody Biomass: A High-Level Overview - Marin Dujmović; Branimir Šafran; Matija Jug; Kristijan Radmanović (Drvna Industrija, 2025)
The global demand to reduce CO2 emissions has led large industrial pollutants, particularly power generation and metallurgical sectors, to search for alternatives to traditional fossil fuels like coal. Wood pellets have emerged as a recognized cleaner alternative. Yet, pellets fall short of coal key properties, notably in calorific value and storage stability. By subjecting the feedstock for wood pellet production, namely woody biomass, to thermal pre-treatments like torrefaction or steam explosion, these limitations can be mitigated. These treatments reduce moisture content, increase energy density, and enhance storage stability, making the wood pellets producedfrom thermally treated feedstock more similar to coal and compatible with existing coal infrastructure. While these pre-treatments offer potential energy savings and other benefits along the process of pellet production and supply chain, they might also necessitate significant capital investments. This review provides a concise overview of thermal pre-treatment technologies, necessary parameters, their impact on treated woody biomass, as well as final characteristics of treated woody biomass.